2008
DOI: 10.1111/j.1745-459x.2008.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Decision Strategies Determined From the Shape of the Same–different Roc Curve: What Are the Effects of Incorrect Assumptions?

Abstract: The literature includes many studies that use the shape of the receiver operating characteristic (ROC) curve derived from the same–different test to ascertain the decision strategy used by the judge: a symmetrical ROC curve indicates a β ‐decision strategy, and an asymmetrical ROC curve indicates a τ ‐decision strategy. These studies have not considered the effect that breaches of the assumptions that underlie the standard same–different model would have on inferences drawn from the shape of the ROC curve. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…There are two major decision strategies used in the process of the same-different judgments: the s-decision strategy, and the b-decision strategy. Although the results obtained from same-different tests with simple stimuli are commonly analyzed using s-strategy, several studies have reported that a b-strategy can also be used for same-different tests for food discrimination (Lee et al, 2007;Lee, van Hout, & Hautus, 2007;Hautus, O'Mahony, & Lee, 2008). Thus it is important to uncover the decision strategy that is being used in the present consumer same-different discrimination tests.…”
Section: 52mentioning
confidence: 95%
See 1 more Smart Citation
“…There are two major decision strategies used in the process of the same-different judgments: the s-decision strategy, and the b-decision strategy. Although the results obtained from same-different tests with simple stimuli are commonly analyzed using s-strategy, several studies have reported that a b-strategy can also be used for same-different tests for food discrimination (Lee et al, 2007;Lee, van Hout, & Hautus, 2007;Hautus, O'Mahony, & Lee, 2008). Thus it is important to uncover the decision strategy that is being used in the present consumer same-different discrimination tests.…”
Section: 52mentioning
confidence: 95%
“…The application of the ROC curve for analysis in food sensory science is reviewed in and the studies that used the shape of the ROC curve derived from the same-different test to investigate the decision strategy used by the subjects were reviewed in Hautus, O'Mahony, and Lee (2008). To determine the best fitted strategy (model) for the ROC curve, the goodness-of-fit statistic (v 2 ) and the probability that the data arose from the strategy fitted given that the strategy was correct (p) were noted.…”
Section: 52mentioning
confidence: 99%
“…It is not exactly the same shape as the equal variance s-criterion curve, but it is close (Hautus, O'Mahony, & Lee., 2008;O'Mahony and Hautus, 2008). It is logically possible, although unlikely, with the ROC analysis currently being used, that detection of a s-strategy (equal variance) might be a false result; it might be the detection of a b-strategy with unequal variance.…”
Section: Judge Total Number Of Sessionsmentioning
confidence: 85%
“…Irwin, Hautus, and Stillman (1992) reviewed ROC curves (Green & Swets, 1974) and some of the drawbacks of R-Index measurement for methods that induced a b-criterion. O'Mahony and and Hautus, O'Mahony and Lee (2008) reviewed the use of ROC curves and described how their shapes could be used to indicate whether judges were using a cognitive strategy that involved a b-or a s-criterion. Irwin et al (1993) demonstrated how ROC curves, derived from same-different tests for orange drinks, were best fitted assuming a cognitive strategy that used a s-criterion.…”
Section: Introductionmentioning
confidence: 99%
“…While this is an unlikely experiment from the perspective of a psychophysicist, experiments of this kind are conducted frequently in the area of sensory evaluation. The goal here is to establish the sensitivity of the observer to stimuli (usually food products or beverages) under the normal conditions of consumption (see Hautus, O'Mahony, & Lee, 2008, for a description of this usage). It is in this context that the duo-trio procedure is frequently employed, and further research is required to determine whether or not observers use the comparison-of-distances strategy in this context.…”
Section: Resultsmentioning
confidence: 99%